A obra ficcional e jornalística do escritor António de Alcântara Machado: letras e imagens - Carmo, Eduardo Benzatti do (2004)
This thesis presents the non dissociable relationship between the life and works of the writer António de Alcântara Machado. Being and creation are shown as complementary movements that furnish a sketch of the outlines of an influential personality of the modernist movement of São Paulo. The resulting image is not, and cannot be a complete one. Born in a traditional family, the author became a strict and coherent man in his political, ethical and esthetical stances, all the while suffering through uncertainties and contradictions concerning religious matters and his personal sentimental life. To unveil this close relationship was not the only goal of this study. The manifold nature of his production reveals the intellectual curiosity and restlessness driving him onwards. Many writing-related activities were unearthed during the research: journalism, theatrical, musical and literary reviews, newspaper articles, short stories, novels, and unfinished plays. Once again we find a complementary link between the journalistic and literary work. Many other facets of the author were also recalled, from enterpreneur to politician. Researching deeply, we sought to locate a significative amount of texts produced by the author, as a newspaper man, and as a proselityzer of the modernist cause. Reviewing such a vast work, interpreting it according to new viewpoints, and making it available to recent generations justifies all of the effort expended. The focus of attention of the sudy fell on the relationship between his writings and the production of images. From a single snapshot to the cinema, from a caricature to an animated feature, the plots of his narratives were built welding a style that evokes a profusion of images of a diverse nature. At the conclusion, our supposition is clearly proven: it is only possible to know the life of a man when we get to know his ideas and his work, just as his works can only be wholly understood when every nuance of it has been aprehended. To achieve this purpose, the investigative method employed were the three principles of complex thinking formulated by Edgar Morin: dialogic, recursive and hologrammatic. Those principles, explicitly stated in this study, permeate and provide theoretical support to this thesis. To present the result of all these movements, the study was structured into four chapters: Intimacies, Maps, Journey and Imaginative. They are the pathways of an imaginary itinerary that guided us in a reconstruction of aspects of the life and works of the author. The result is the retrieval and renewal of a creation that must not be forgotten